mTORC1 activity regulates post-translational modifications of glycine decarboxylase to modulate glycine metabolism and tumorigenesis - Rui Liu (Nature Portfolio, 2021)
An increase in glycine decarboxylase (GLDC) activity, a key enzyme for glycine catabolism, has been associated to tumourigenesis. Here, the authors show that mTORC1 activation induces GLDC deacetylation which impairs its ubiquitin-associated degradation leading to increased GLDC activity and tumourigenesis.